279 Medical treatment with ARNI may reduce indications for primary prevention of sudden cardiac death in heart failure with reduced ejection fraction: insights from discover-ARNI, a multicentre Italian register. (8th December 2021) - Pastore, Maria Concetta; Mandoli, Giulia Elena; Giannoni, Alberto; Benfari, Giovanni; Dini, Frank Lloyd; Rosa, Gianmarco; Pugliese, Nicola Riccardo; Taddei, Claudia; Correale, Michele; Brunetti, Natale Daniele; Magnesa, Michele; Carluccio, Erberto; et al.
Abstract: Aims: This sub-study deriving from a multicentre Italian register (DISCOVER-ARNI) investigated whether sacubitril/valsartan in adjunction of optimal medical therapy (OMT) could reduce the rate of implantable cardioverter-defibrillator(ICD) indications for primary prevention in heart failure with reduced ejection fraction (HFrEF) according to European guidelines indications, and its potential predictors. Methods and results: In this observational study, consecutive patients with HFrEF eligible for sacubitril/valsartan from 13 Italian centres were included. Lack of follow-up or speckle tracking data represented exclusion criteria. Demographic, clinical, biochemical and echocardiographic data were collected at baseline and after 6 months of therapy. Of 351 patients, 225 (64%) were ICD carriers and 126 (36%) were not ICD carriers (of whom 13 had not indication) at baseline. After 6 months of sacubitril/valsartan, among 113 non-ICD carriers despite having baseline left ventricular (LV)EF ≤ 35% and New York Heart Association (NYHA) class = II–III, 69(60%) did not show ICD indications; 44(40%) still fulfilled ICD criteria (Figure 1). Age, atrial fibrillation, mitral regurgitation>moderate, left atrial volume index (LAVi), and LV global longitudinal strain (GLS) significantly varied between the groups. With ROC curves, age ≥ 75 years, LAVi ≥ 42 ml/m 2 and LV GLS ≥ −8.3% were associated with ICD indications persistence (AUC = 0.65, 0.68, and 0.68, respectively). With univariate and multivariate analysis, age and LV GLS emerged as the only significant predictors of ICD indications at follow-up. Conclusions: Sacubitril/valsartan provided early improvement of NYHA class and LVEF, reducing the possible number of implanted ICD for primary prevention in HFrEF. Baseline advanced age and reduced LV GLS were markers of ICD indication despite OMT. Early therapy with sacubitril/valsartan may save infective/haemorrhagic risks and unnecessary costs deriving from ICDs.